2024
DOI: 10.1159/000536570
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Necrotizing Enterocolitis and Late-Onset Sepsis during the COVID-19 Pandemic in Sweden: A Population-Based Cohort Study

Elena Palleri,
Anna Svenningsson,
Laszlo Markasz
et al.

Abstract: <b><i>Introduction:</i></b> The effect of the pandemic restrictions in the NICUs is not well studied. Necrotizing enterocolitis (NEC) is characterized by intestinal inflammation and bacterial invasion. This study aimed to investigate whether the incidence of NEC has changed during the COVID-19 pandemic in Sweden and whether it was associated with a change in the frequency of extremely preterm births. <b><i>Methods:</i></b> Data were retrieved from the Swedish Neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
1
1
1
Order By: Relevance
“…GA, gestational age. inconsistent with the above findings but similar to those of our study (18). In the first two weeks of life, hospital regimens led to a centre-specific, distinct cluster of faecal microbiome formation in the gut microbiome of very-low-birth-weight infants (17).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…GA, gestational age. inconsistent with the above findings but similar to those of our study (18). In the first two weeks of life, hospital regimens led to a centre-specific, distinct cluster of faecal microbiome formation in the gut microbiome of very-low-birth-weight infants (17).…”
Section: Discussionsupporting
confidence: 91%
“…Indrio F ( 17 ) found that pandemic-related NICU hygiene policies did not reduce the occurrence of NEC in very-low-birth-weight infants in four Italian NICUs. However, the results of some studies are inconsistent with the above findings but similar to those of our study ( 18 ). In the first two weeks of life, hospital regimens led to a centre-specific, distinct cluster of faecal microbiome formation in the gut microbiome of very-low-birth-weight infants ( 17 ).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation